Karsinoma Nasopharynx dan infeksi EBV di Indonesia; analisis aspek klinis, Patologi dan Biomolekular - Notopuro, Harianto; A Kentjono, Widodo; Handajani, Retno; B Notopuro, Paulus (Lembaga Penelitian Universitas YARSI, 2008)
Nasopharyngeal carcinoma (NPC) is a unique epithelial malignancy that occurs at a high frequency in certain regions of Southeast Asia. Previous study revealed the association between Epstein Barr Virus (EBV) and to a lesser extent, Human Papilloma Virus (HPV) with NPC. The role of the EBV in the pathogenesis of NPC was further supported by the recovery response of the tumor cells after being treated with EBV-specific T lymphocytes. The present study aims to determine the frequency distribution of EBV infection among the pathologically confirmed NPC patients and healthy control in Surabaya, Indonesia. The presence of Human Papilloma. Virus infection (HPV) was also analysed. The results indicated that EBV DNA existed in the 88% of the nasopharyngeal tissue biopsies of 25 NPC patients and none in the 10 healthy controls, and the difference was statistically significant.Analysis of the mononuclear cells of peripheral blood revealed that 60% of the 25 NPC patients carried EBV DNA whereas in control group 20% was found to be positive and the difference was statistically significant. Although a high positive rate EBV-DNA was detected in NPC patients, additional environmental and genetic factors must still be considered. Nevertheless, no HPV-DNA was detected from mononuclear cells of peripheral blood and nasopharyngeal tissue of the two groups. By this study there was no coexistence between the infection of EBV and HPV which promote carcinogenesis in NPC. Analysis using LMP1-DNA in tumor cell biopsies indicated that 72% of the NPC patients yielded PCR products and none of the healthy control, the difference was statistically significant. In conclusion the findings confirm the tight association between the EBV and NPC in Indonesia and that the specific presence of LMP1-DNAs in the tumor cells strongly indicates the important role of EBV in the pathogenesis of NPC. Coexistence of EBV and HPV infections was not found in NPC cases in Indonesia.